Immunotherapy in People With HIV and Cancer - Puronen, Camille E.; Ford, Emily S.; Uldrick, Thomas S. (Frontiers in Immunology, 2019)
HIV infection alters the natural history of several cancers, in large part due to its effect on the immune system. Immune function in people living with HIV may vary from normal to highly dysfunctional and is largely dependent on the timing of initiation (and continuation) of effective antiretroviral therapy (ART). An individual's level of immune function in turn affects their cancer risk, management, and outcomes. HIV-associated lymphocytopenia and immune dysregulation permit immune evasion of oncogenic viruses and premalignant lesions and are associated with inferior outcomes in people with established cancers. Various types of immunotherapy, including monoclonal antibodies, interferon, cytokines, immunomodulatory drugs, allogeneic hematopoietic stem cell transplant, and most importantly ART have shown efficacy in HIV-related cancer. Emerging data suggest that checkpoint inhibitors targeting the PD-1/PD-L1 pathway can be safe and effective in people with HIV and cancer. Furthermore, some cancer immunotherapies may also affect HIV persistence by influencing HIV latency and HIV-specific immunity. Studying immunotherapy in people with HIV and cancer will advance clinical care of all people living with HIV and presents a unique opportunity to gain insight into mechanisms for HIV eradication.